1995
DOI: 10.1016/1074-5521(95)90100-0
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between an endangered North American tree and an endophytic fungus

Abstract: The filamentous fungus, P. microspora, has an endophytic-pathologic relationship with T. taxifolia. The fungus resides in the inner bark of symptomless trees, and physiological or environmental factors could trigger its pathological activity. P. microspora produces the phytotoxins pestalopyrone, hydroxypestalopyrone, and pestaloside which give rise to the disease. Pestaloside, which also has antifungal activity, could reduce competition from other fungal endophytes within the host.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(50 citation statements)
references
References 12 publications
3
45
0
2
Order By: Relevance
“…Its UV spectrum with maximum absorption bands at λ max 213, 226, 251 and 320 nm indicated that 1 had a conjugated pyrone chromophore (Lee et al, 1995). The IR spectrum showed absorption bands at 3394 and 1714 cm -1 for hydroxyl and conjugated carbonyl groups, respectively.…”
Section: Resultsmentioning
confidence: 98%
“…Its UV spectrum with maximum absorption bands at λ max 213, 226, 251 and 320 nm indicated that 1 had a conjugated pyrone chromophore (Lee et al, 1995). The IR spectrum showed absorption bands at 3394 and 1714 cm -1 for hydroxyl and conjugated carbonyl groups, respectively.…”
Section: Resultsmentioning
confidence: 98%
“…Scientists all over the world have studied taxol production on various platforms including chemical synthesis, plant cell and tissue culture (Table 1) (Fett-Neto et al 1992;Wang and Zhong 2002;Wang et al 2007a, b, c;Khosroushahi et al 2006;Croteau et al 2006), endophytic fungi (reviewed by Visalakshi and Muthumary 2010), microbial fermentation, and so on (Jennewein and Croteau 2001;Frense 2007). Zhou et al (2010) reviewed that microbial fermentation of endophytic fungi is a new and feasible approach to the production of taxol (Stierle et al 1993;Lee et al 1995;Li et al 1996;Huang et al 2001;Wang et al 2000;Sun et al 2008). …”
Section: Taxolmentioning
confidence: 98%
“…Thus, endophytes may play an important role in their host's growth and the formation of secondary metabolites related to plant defense. However, existing research into these relationships mainly concentrates on ecological associations (Lee et al 1995). There have been no reports of application of endophyte-plant associations based on natural ecosystems in paclitaxel production.…”
Section: Introductionmentioning
confidence: 99%